2018
DOI: 10.1017/s0022149x18000044
|View full text |Cite
|
Sign up to set email alerts
|

Sclerocollum saudii Al-Jahdali, 2010 (Acanthocephala: Cavisomidae) as a sentinel for heavy-metal pollution in the Red Sea

Abstract: Currently, fish helminth parasites, especially cestodes and acanthocephalans, are regarded as sentinel organisms to elucidate metal pollution in aquatic ecosystems. Here, 34 specimens of the fish Siganus rivulatus were collected in the Red Sea, from a seriously polluted, small lagoon named Sharm-Elmaya Bay, at Sharm El-Sheikh, South Sinai, Egypt; 22 (64.7%) were infected by Sclerocollum saudii (Acanthocephala: Cavisomidae). Thus, 22 natural infrapopulations (26-245 individuals) of this parasite were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Similarly, acanthocephalan worms, due to their armed proboscises, adversely affect the health of their fish hosts by damaging the nature of intestinal tissue in these hosts at the attachment sites, causing severe histological and histopathological changes [15][16][17][18][19][20][21][22]. In contrast, several studies [13,23,24,31] have pointed to a beneficial impact of acanthocephalans on their fish hosts because these worms have much higher potential and capacity than their fish hosts to bioaccumulate different metals, especially the toxic ones, and thus can minimize the amounts of heavy metals in the tissues of these fish hosts. However, numerous studies [13,[26][27][28][29]32,34] revealed that metal concentrations in the tissues of acanthocephalan-infected fish were significantly less than those of uninfected conspecifics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, acanthocephalan worms, due to their armed proboscises, adversely affect the health of their fish hosts by damaging the nature of intestinal tissue in these hosts at the attachment sites, causing severe histological and histopathological changes [15][16][17][18][19][20][21][22]. In contrast, several studies [13,23,24,31] have pointed to a beneficial impact of acanthocephalans on their fish hosts because these worms have much higher potential and capacity than their fish hosts to bioaccumulate different metals, especially the toxic ones, and thus can minimize the amounts of heavy metals in the tissues of these fish hosts. However, numerous studies [13,[26][27][28][29]32,34] revealed that metal concentrations in the tissues of acanthocephalan-infected fish were significantly less than those of uninfected conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…This process may affect the physiology of the fish hosts by lowering the amount of metals available in their intestine before absorption through the intestinal wall to other organs. If these metals are toxic, then the parasites have a beneficial impact on their fish hosts, by minimizing the amounts of these metals in their tissues [13,23,30,31]. Confirming this, several studies have shown that metal concentrations in the tissues of acanthocephalan-infected fish were significantly less than those of uninfected conspecifics [13,28,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations